Cytomegalovirus reactivation in hepatitis B and C infected population - Talić Drlje, Ivana; Šušak, Božo; Arapović, Jurica (The Journal of Infection in Developing Countries, 2025)
Introduction: Cytomegalovirus (CMV) seroprevalence varies globally. This study aimed to detect CMV seroprevalence and reactivation among patients who had been exposed to hepatitis B virus (HBV) or hepatitis C virus (HCV). Methodology: The study was conducted between 2017 and 2022 and included adult participants who were serologically diagnosed with hepatitis B (63 participants) or hepatitis C (69 participants), as well as 132 control respondents. CMV IgG and IgM levels were measured for all 264 respondents; CMV IgG avidity was further determined for those who tested positive for CMV IgG and IgM. Results: The total CMV IgG seroprevalence observed in the study was 95.4%, with 98.5% in HCV-positive, 96.8% in HBV-positive, and 95.2% in control respondents; and with a slightly higher prevalence in women (97.1%) compared to men (94.9%). The overall CMV reactivation rate among anti-HCV positive respondents was 2.9%. Although no significant difference was found in the reactivation rate of CMV between anti-HCV positive and negative respondents, the reactivation rate of CMV within the subgroup of HCV RNA positive individuals was higher at 4.4%. In contrast, no CMV reactivation was observed in the respondents without detectable HCV RNA. No CMV reactivation was detected in the HBV group. Conclusions: This study did not confirm a higher reactivation rate of CMV in HBV- or HCV-positive respondents compared to the control cases. Given the high CMV seroprevalence among adults in Bosnia and Herzegovina, future research should include CMV DNA testing for more accurate assessment.